Effects of sociocultural and economic factors on social entrepreneurship and sustainable development - María Teresa Méndez Picazo; Miguel Angel Galindo Martín; María Soledad Casta\~no Martínez (Journal of Innovation & Knowledge (JIK), 2021)
Concern about environmental problems has led to more attention being paid to the sustainable development objective. Social entrepreneurship, and entrepreneurship in general, show a direct relationship with this objective, due mainly to the activities carried out by entrepreneurs regarding the development of new products, the search for new markets, and the introduction of innovations. Because of this, it is important to identify the variables that influence both types of entrepreneurship to adequately design measures to stimulate sustainable development through these activities. These variables can be grouped into two groups: sociocultural factors and economic factors. The objective of this paper is to analyze the behavior of these two groups over general entrepreneurship and social entrepreneurship, in addition to the impact of these two types of entrepreneurship on sustainable development. To carry out this analysis, we have developed an empirical analysis with structural equations for the case of 15 OECD countries between 2015 and 2016.
Keywords: L26; L31; O40; Q01; O43; E02; 650; Corruption; Partial least squares (PLS); Social entrepreneurship; Sociocultural factors; Sustainable development